Cecropin AD reduces viral load and inflammatory response against H9N2 avian influenza virus in chickens - Zhang, Taiming; Liu, Zhenyi; Zhi, Yan; Zhao, Xinping; Du, Mengze; Zhang, Qian; Zhang, Tao; Hu, Ge (Frontiers in Veterinary Science, 2024)
Introduction This study focuses on evaluating the therapeutic efficacy of cecropin AD, an antimicrobial peptide, against H9N2 avian influenza virus (AIV) in chickens. Given the global impact of H9N2 AIV on poultry health, identifying effective treatments is crucial. Methods To assess the impact of cecropin AD, we conducted in vivo experiments involving 108 5-week-old chickens divided into control, infected, and various treatment groups based on cecropin AD dosage levels (high, medium, and low). The methodologies included hemagglutination (HA) tests for viral titers, histopathological examination and toluidine blue (TB) staining for lung pathology, real-time PCR for viral detection, and enzyme-linked immunosorbent assays for measuring serum levels of inflammatory markers. Results The findings revealed that cecropin AD substantially reduced lung pathology and viral load, especially at higher dosages, comparing favorably with the effects seen from conventional treatments. Moreover, cecropin AD effectively modulated mast cell activity and the levels of inflammatory markers such as IL-6, TNF-α, IFN-γ, and 5-HT, indicating its potential to diminish inflammation and viral spread. Discussion Cecropin AD presents a significant potential as an alternative treatment for H9N2 AIV in chickens, as evidenced by its ability to lessen lung damage, decrease viral presence, and adjust immune responses. This positions cecropin AD as a promising candidate for further exploration in the management of H9N2 AIV infections in poultry.